The diversity of wild edible plants used by community living around Mount Merapi National Park, Central Java, Indonesia - KHOTROTUN NIDA FARIKHA; LATHIFA PUTRI WIEDHYA SYAHRANI; LUNETTA KHALIS ALFIYAH; LUTHFIA LUTHFIA; MURNI NURWULANDARI; IRFAN ABU NAZAR; EDI JUNAEDI; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2024)
Abstract. Farikha KN, Syahrani LPW, Alfiyah LK, Luthfia, Nurwulandari M, Nazar IA, Junaedi E, Setyawan AD. 2024. The diversity of wild edible plants used by community living around Mount Merapi National Park, Central Java, Indonesia. Biodiversitas 25: 3041-3049. Mount Merapi National Park is one of the conservation areas in Indonesia that serves as habitat for various species of wild plants with ecological value and social benefits for local communities. However, the impacts of social, economic, and environmental changes have led to a decline in community interest in utilizing the presence of wild plants there. This research aims to document the diversity of wild edible plants used by local community living around Mount Merapi National Park in Kemalang Sub-district, Klaten District, Central Java, Indonesia. Data collection involved physical observation and semi-structured questionnaires to 58 respondents. Data analysis was carried out by classifying plants based on their local names, families, scientific names, growth forms, parts utilized, uses, and conservation status. This study documented 45 species of wild edible plants belonging to 32 families with the dominance of the Zingiberaceae family. Wild edible plants are utilized as food sources, cooking ingredients, and traditional medicine with leaves being the most commonly utilized part. Andrographis paniculata is most frequently utilized by the community. Based on the IUCN Red List, there are 20 wild edible species categorized as Least Concern, 13 species Not Evaluated, 11 species Data Deficient, and 1 species Endangered.